(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
This paper analyzes the cases of limitation of therapeutic effort regarding minors when there is a conflict between the medical team and the legal representatives. In this regard, it describes the complex legal framework for this matter under Spanish law and analyzes and assess the legal issues that Andrea’s case raises.